2018
DOI: 10.1080/10245332.2018.1423671
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between obesity and iron deficiency anemia: is there a role of hepcidin?

Abstract: Our study suggests that hepcidin levels do not contribute to the development of iron deficiency anemia in pediatric obese individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
1
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 32 publications
8
45
1
8
Order By: Relevance
“…In this study similar concentrations of ferritin and iron were found in obese and non-obese groups. This is similar to the results obtained by Aeberli et al [ 14 ], Sanad et al [ 16 ] and Sal et al [ 19 ]. Ferritin is considered an indicator for determining iron deficiency, but serum ferritin levels had weak correlations with serum iron levels and transferrin saturation [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study similar concentrations of ferritin and iron were found in obese and non-obese groups. This is similar to the results obtained by Aeberli et al [ 14 ], Sanad et al [ 16 ] and Sal et al [ 19 ]. Ferritin is considered an indicator for determining iron deficiency, but serum ferritin levels had weak correlations with serum iron levels and transferrin saturation [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…One of the proposed causes of hypoferritinemia in obesity is deficient iron intake from an iron poor diet [ 13 ], but some studies suggest this is not the cause [ 14 , 15 ]. Several researchers have demonstrated that iron deficiency is associated with the higher circulation of hepcidin in obese subjects, including children and adolescents [ 16 , 17 , 18 , 19 ]. Other studies showed lower values of hepcidin-25 and hyperferritinemia in overweight and obese children compared with their normal-weight counterparts [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because transferrin is an acute-phase protein, it is characterised by severe reductions in the early period after major trauma. [19] In the literature, to our knowledge, no studies related to the relationship between physiotherapy and transferrin has been found. Pouramir et al [20] reported that long-term exercise may drain iron deposits and cause…”
Section: Discussionmentioning
confidence: 97%
“…Jika metabolisme besi terganggu, maka terjadilah anemia. (Sal et al, 2018;McClung and Karl, 2008 ;Lopez et al, 2011) Timbunan lemak pada hati juga dapat memicu pembentukan peroksida lipid yang pada akhirnya akan mempengaruhi proses metabolisme besi sehingga akan terjadi radikal bebas. Hal ini menyebabkan sintesis Hb tidak dapat berjalan dengan sempurna.…”
Section: A Indeks Massa Tubuhunclassified